2017
DOI: 10.1590/1414-431x20175976
|View full text |Cite
|
Sign up to set email alerts
|

Therapy of tacrolimus combined with corticosteroids in idiopathic membranous nephropathy

Abstract: We evaluated the efficacy and safety of tacrolimus (TAC) combined with corticosteroids in treating patients with idiopathic membranous nephropathy (IMN). One hundred seventy-seven biopsy-proven IMN patients were recruited in this retrospective clinical study. Sixty patients received TAC (target blood concentration of 4–8 ng/mL) and 117 patients received daily cyclophosphamide (CYC, 100 mg) combined with prednisone. Remission rates at the end of the first, second and third month in the TAC group were significan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
14
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(24 citation statements)
references
References 27 publications
5
14
2
Order By: Relevance
“…TR rates in the TAC group and TAC + Pred group were 77.5% and 80.4%, respectively. TR rates in both groups at the 12th month follow‐up were similar and satisfying, and the results are consistent with previous studies . The above results were further confirmed by multivariate logistic regression.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…TR rates in the TAC group and TAC + Pred group were 77.5% and 80.4%, respectively. TR rates in both groups at the 12th month follow‐up were similar and satisfying, and the results are consistent with previous studies . The above results were further confirmed by multivariate logistic regression.…”
Section: Discussionsupporting
confidence: 91%
“…A number of studies have shown that TAC, either monotherapy or in combination with corticosteroids, was effective in treating IMN patients . In clinical practice, TAC based regimen has been preferred by young adults nowadays.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The difference in the infection incidence between the CHL group and the TAC group was not significant (P > 0.10). In addition, a slightly higher proportion of nausea and vomiting was found in the CHL group (11,15.3%) than found in the TAC group (5, 6.8%), with a P value of the c 2 test of 0.099. More details are shown in Table 5 and Fig.…”
Section: Adverse Effects Of Induction or Maintenance Therapymentioning
confidence: 78%
“…Recently, studies have demonstrated the significant efficacy of nitrogen mustard or TAC in treating patients with idiopathic membranous nephropathy (IMN) [14][15][16], which showed a significant remission with a reduction in proteinuria or plasma creatinine in IMN patients and a reduced probability of developing end-stage renal disease [17,18]. Additionally, existing evidence supports the use of a combination of steroid and alkylating agents, such as nitrogen mustard [19].…”
Section: Introductionmentioning
confidence: 99%